Sharia Governance and ESG Performance: Evidence from Islamic Financial Institutions - Hilman; Afidah Nur Aslamah (Jurnal Ilmiah Ekonomi Islam, 2025)
The global shift toward sustainability-oriented finance has encouraged Islamic financial institutions to integrate Environmental, Social, and Governance (ESG) principles into their operational practices. Meanwhile, Shariah Governance has traditionally been positioned primarily as a mechanism to oversee shariah compliance, and empirical evidence regarding its relationship with ESG performance remains limited. This study aims to analyze the impact of Shariah Governance on the Environmental, Social, and Governance (ESG) performance of Islamic commercial banks in Indonesia during the period of 2021–2024. Additionally, this study also explores the role of bank characteristics, such as bank size (total assets), profitability (Return on Assets/ROA), and bank age, in controlling the relationship between Shariah Governance and ESG performance. Using a quantitative approach, this research employs secondary data obtained from annual reports, sustainability reports, and governance reports of Islamic financial institutions listed on the Indonesian Sharia Stock Index. Shariah Governance and ESG performance were measured through content analysis, while model testing was conducted using SEM-PLS with SmartPLS 4.0. The results indicate that the model explains 43% of the variance in ESG performance through Shariah Governance and control variables including bank size, profitability, and bank age. Key findings from the inner model show that Shariah Governance has a negative and significant effect on ESG performance, while profitability has a positive and significant effect. Bank size shows no significant influence, whereas bank age has a negative and significant effect on ESG performance. These findings suggest that strengthening existing Shariah Governance structures does not automatically enhance ESG performance, and that younger and more profitable institutions tend to be more progressive in adopting sustainability agendas. The study concludes that a reorientation of the Shariah Governance framework is needed so that it not only emphasizes formal compliance but also explicitly integrates sustainability objectives aligned with the maqashid al-shariah. Alif, Y. S., Fitri, S. R., & Pertiwi, H. P. (2025). Implementation of ESG (Environmental, Social, Governance) in Islamic Banks a Critical and Strategic Review. Al-Muwazanah: Indonesian Journal of Islamic Economics, 1(1), 13–25. Arrazi, M. F. (2023). Konsep shariah governance pada lembaga keuangan syariah:(Suatu tinjauan komparatif). MIZANUNA: Jurnal Hukum Ekonomi Syariah, 1(2), 17–30. Boudawara, Y., Toumi, K., Wannes, A., & Hussainey, K. (2023). Shari’ah governance quality and environmental, social and governance performance in Islamic banks. A cross-country evidence. Journal of Applied Accounting Research, 24(5), 1004–1026. Buallay, A. (2019). Is sustainability reporting (ESG) associated with performance? Evidence from the European banking sector. Management of Environmental Quality: An International Journal, 30(1), 98–115. Islamic Financial Services Board (IFSB). (2025). IFSB-31 Guiding Principles For Efective Supervision Of Shari’ah Governance. www.ifsb.org Khan, S., Nisar, M., Sohail, M., Awan, M. M. U., Rehman, A. U., & Yasir, M. (2023). Impact of islamic corporate governance on sustainability performance in Islamic banks of Pakistan: moderating role of insider ownership and institutional ownership. International Journal of Business and Economic Affairs, 8(2), 52–65. Milena, W., & Stefan, A. (2024). Enhancing ESG Performance in Islamic Banks: The Impact of Shari’ah Governance Quality Across Countries. Journal International Economic Sharia, 1(3), 158–174. Puspitasari, N. D., & Kasri, R. A. (2023). Shariah board governance and sustainability performance: analysis of sharia banking in Indonesia. Jurnal Ekonomi & Studi Pembangunan, 24(2), 458–478. Siregar, R. (2025). ESG and Islamic Accounting for Sustainable Islamic Finance: A Qualitative Study. Jurnal Ilmiah Akuntansi Kesatuan, 13(3), 555–566.